Leukocyte-Dependent Regulation of Cardiac Fibrosis - Okyere, Ama Dedo; Tilley, Douglas G. (Frontiers in Physiology, 2020)
Cardiac fibrosis begins as an intrinsic response to injury or ageing that functions to preserve the tissue from further damage. Fibrosis results from activated cardiac myofibroblasts, which secrete extracellular matrix (ECM) proteins in an effort to replace damaged tissue; however, excessive ECM deposition leads to pathological fibrotic remodeling. At this extent, fibrosis gravely disturbs myocardial compliance, and ultimately leads to adverse outcomes like heart failure with heightened mortality. As such, understanding the complexity behind fibrotic remodeling has been a focal point of cardiac research in recent years. Resident cardiac fibroblasts and activated myofibroblasts have been proven integral to the fibrotic response; however, several findings point to additional cell types that may contribute to the development of pathological fibrosis. For one, leukocytes expand in number after injury and exhibit high plasticity, thus their distinct role(s) in cardiac fibrosis is an ongoing and controversial field of study. This review summarizes current findings, focusing on both direct and indirect leukocyte-mediated mechanisms of fibrosis, which may provide novel targeted strategies against fibrotic remodeling.